Communicating Organizational Strategy to Employees Using the Balanced Scorecard (BSC): Case Study of a Malaysian Company (Journal of Business Management and Accounting, 2018)
Communicating organizational strategy to employees has been identified as one of the factors that influence success of strategy implementation in an organization. This study presents a case study of the use of BSC as a strategy communication tool in the strategy implementation process of a large Malaysian service provider. Specifically, the study explores how the BSC was used to facilitate strategy communication from the top to the lower management team, the factors affecting its effectiveness and its implication. Data was collected using interviews with 30 managers from various management levels and observations in eighteen meetings and BSC training sessions. Findings of this study show that, if applied properly, the strategy map and scorecard improve strategy communication among the different management levels. It was also found that among the factors that may influence the effectiveness of it usage are the content of the maps and scorecard and the channel of communication used to convey the information. In addition, this paper provides evidence of the application of BSC as a communication tools.